THEATRE PERFORMANCE COMMUNICATION FROM THE PERSPECTIVE OF THEATRE SEMIOTICS - Nur Sahid (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2013)
This article investigates the processes of communicating performance elements including word sign systems, facial expressions, tones, gestures, motions, make-up, hair styles, costumes, props, settings, lighting, music, voice or sound effects from the performers to the audience. The success of a theatrical performance actually depends on the successful communication of these elements by the performers. This study adopts the perspective of theater semiotics. Hopefully this article can benefit theater creators in communicating performance codes and messages to the audience. Thus, a theatrical performance can be a productive communication between them and the audience.